Doping Effects in CMOS‐compatible CoSi Thin Films for Thermoelectric and Sensor Applications. Issue 14 (10th June 2020) - Krishna Nichenametla, Charan; Calvo, Jesus; Riedel, Stefan; Gerlich, Lukas; Hindenberg, Meike; Novikov, Sergej; Burkov, Alexander; Kozelj, Primož; Cardoso‐Gil, Raul; Wagner‐Reetz, Maik
Abstract : Abstract . We report on semi‐metallic cobalt monosilicide (CoSi) as a CMOS‐compatible thermoelectric (TE) material and discuss the effect of n ‐ and p ‐type dopants on its transport properties. Thin films of CoSi are developed using chemical vapor deposition tools and subsequent rapid thermal processing. Film properties such as microstructure, crystallinity and elemental distribution are studied via electron microscopy, X‐ray diffraction and time‐of‐flight secondary ion mass spectroscopy. Doping silicon with boron prior to silicidation impedes the Co‐Si diffusion process, while phosphorus atoms distribute uniformly in silicides with no voids or agglomerations. CoSi makes a suitable n ‐type TE candidate and provides an alternative to Si or SiGe materials. Transport properties of undoped CoSi exhibit a linear dependence within the investigated temperature window, whereas dopants in CoSi increase the number of electron carriers that contribute to charge transport and thereby influence the Seebeck coefficient. Thus, TE characteristics of thin CoSi films can be tuned via (i) the type of dopants used and/or (ii) varying the residual silicon thickness post silicidation. Abstract :